A comprehensive investigation of Clerodendrum Infortunatum Linn. using LC-QTOF-MS/MS metabolomics as a promising anti-alzheimer candidate - Fatma Atef; Mostafa A. Abdelkawy; Basma M. Eltanany; Laura Pont; Ahmed M. Fayez; Mohamed F. Abdelhameed; Fernando Benavente; Inas Y. Younis; Asmaa M. Otify (Scientific Reports)
Abstract Alzheimer’s disease (AD) poses a global health challenge, demanding innovative approaches for effective treatments. Clerodendrum infortunatum Linn. (Lamiaceae) is a shrub traditionally used as a medicinal plant to treat inflammation, skin diseases, and bronchitis. This study aims to identify the main bioactive metabolites in C. infortunatum using LC-QTOF-MS/MS and investigate its potential in protecting against cognitive decline in rats with scopolamine-induced AD disease. Metabolite profiling was performed on the methanol extract of the plant’s aerial parts using LC-QTOF-MS/MS. The inhibitory activity of the acetylcholinesterase enzyme was measured in vitro. To evaluate the cognitive effects, the methanol extract was orally administered at three doses (100, 200, and 400 mg/kg) to scopolamine-induced AD rats, and their cognitive functions were assessed using the novel object recognition test. Additionally, acetylcholinesterase enzyme activity, as well as the levels of acetylcholine, dopamine, noradrenaline, glutathione, malondialdehyde, tumor necrosis factor-α, interleukin-1β, and amyloid-β in the rat hippocampus, were measured using ELISA, followed by histopathological evaluation. A total of 79 metabolites, spanning various chemical classes, such as organic acids, phenolic acids, phenylpropanoids and phenylethanoids, flavonoids, coumarins, other phenolics, and fatty acids and their derivatives, were identified. The results showed that the extract promoted enhanced cognitive functions in the novel object recognition test. Scopolamine administration significantly altered the acetylcholinesterase enzyme activity and biomarker levels in the rat’s hippocampus. However, treatment with C. infortunatum at 200 and 400 mg/kg almost restored these neurotransmitter levels to normal, which was further confirmed by histopathological analysis. This study demonstrates the therapeutic potential of C. infortunatum in mitigating cognitive decline in AD, with its first metabolite profiling revealing a range of bioactive compounds. The extract improved cognitive function in scopolamine-induced AD rats, restored acetylcholinesterase activity, normalized neurotransmitter levels, and reduced oxidative stress and inflammation. These findings suggest that C. infortunatum is a promising candidate for the development of natural therapies targeting AD.